2018
DOI: 10.1021/acs.iecr.7b04793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Concentrated Salt on the Droplet Size and Mass Transfer Coefficient in a Stirred Liquid–Liquid Reactor

Abstract: This work addressed liquid−liquid mass transfer for actual industrial conditions of high pH with coexisting salt. The Sauter mean diameter was determined from the direct measurement of a chlorobenzene droplet size using a borescope system. At a high NaOH concentration, the droplet size decreased significantly due to the reduced density difference between two phases, and it further decreased when NaOH and NaCl coexisted. A Sauter mean diameter correlation with a density difference term was proposed, and it succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…After the complete replacement of the system gas by oxygen, the object gas was distributed, and the variation of DO in the system liquid was measured using a polarographic DO meter (Hanna Instruments, HI98193). The collected DO data were transferred to the PC, and the experimental k l a was calculated by the following equation 36,46,47 Bubble velocity was measured by a stopwatch. Once a bubble was released above the sparger, exact time measurement began.…”
Section: Methodsmentioning
confidence: 99%
“…After the complete replacement of the system gas by oxygen, the object gas was distributed, and the variation of DO in the system liquid was measured using a polarographic DO meter (Hanna Instruments, HI98193). The collected DO data were transferred to the PC, and the experimental k l a was calculated by the following equation 36,46,47 Bubble velocity was measured by a stopwatch. Once a bubble was released above the sparger, exact time measurement began.…”
Section: Methodsmentioning
confidence: 99%
“…As such salt addition to a suspension alters its physiochemical properties (salinity effect, A). It's been earlier reported that addition of salt leads to increase in oil droplet size as it induces the thinning of the Electric Double Layer (EDL) because of the electrostatic screening effect of salt (Park et al, 2018). The EDL prevents the coalescence of oil droplets by electrostatic repulsion, by its thinning oil droplets tend to combine.…”
Section: Droplet Sizementioning
confidence: 99%
“…Under this circumstance, the volume fraction of NaI solution is 50%. For the homogenization of each phase, an overhead stirrer unit and double Rushton impellers are used, and each impeller is placed at the half of each liquid depth, which is also adopted by Park et al 25 to estimate the partition coefficient, as shown in Figure 6. Impeller speed N is set as 50 rpm, which is slow enough to maintain a flat interface and prevent droplet formation.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Fang et al 23 studied the mass transfer in a liquid−liquid−solid system and found that the presence of inert solid particles enhanced the liquid−liquid mass transfer at high rotational speeds. The mass transfer characteristics and hydrodynamics of the liquid− liquid laminar flow in microchannels were studied by Zhang et al 24 Park et al 25 studied the effect of pH and concentrated salt solution on the mass transfer coefficient in a stirred liquid− liquid reactor, and they found that the mass transfer coefficient increased with the increase of NaOH and NaCl concentrations. Some previous works used acoustic-assisted technology to study the liquid−liquid mass transfer.…”
Section: Introductionmentioning
confidence: 99%